Scaffold-free three-dimensional cell culture utilizing micromolded nonadhesive hydrogels - Anthony P. Napolitano; Dylan M. Dean; Alan J. Man; Jacquelyn Youssef; Don N. Ho; Adam P. Rago; Matthew P. Lech; Jeffrey R. Morgan (BioTechniques)
Techniques that allow cells to self-assemble into three-dimensional (3-D) spheroid microtissues provide powerful in vitro models that are becoming increasingly popular—especially in fields such as stem cell research, tissue engineering, and cancer biology. Unfortunately, caveats involving scale, expense, geometry, and practicality have hindered the widespread adoption of these techniques. We present an easy-to-use, inexpensive, and scalable technology for production of complex-shaped, 3-D microtissues. Various primary cells and immortal cell lines were utilized to demonstrate that this technique is applicable to many cell types and highlight differences in their self-assembly phenomena. When seeded onto micromolded, nonadhesive agarose gels, cells settle into recesses, the architectures of which optimize the requisite cell-to-cell interactions for spontaneous self-assembly. With one pipeting step, we were able to create hundreds of uniform spheroids whose size was determined by seeding density. Multicellular tumor spheroids (MCTS) were assembled or grown from single cells, and their proliferation was quantified using a modified 4-[3-(4-iodophenyl)-2-(4-nitrophenyl)-2H-5-tetrazolio]-1,3-benzene disulfonate (WST-1) assay. Complex-shaped (e.g., honeycomb) microtissues of homogeneous or mixed cell populations can be easily produced, opening new possibilities for 3-D tissue culture.